Resistensi Perempuan terhadap Victim Blaming dalam Kekerasan Seksual pada Cerpen “Perempuan, Perempuan, Turunkan Rambutmu” - Marta Widyawati (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
Sexual violence against women followed by victim blaming is still common in Indonesia. This is based on the existence of a strong male domination structure that makes it difficult for women to position themselves. This study aims to analyze the forms of sexual violence and victim blaming, and to interpret the resistance that emerged from women to this in the short story "Perawan, Perawan Bawahkan Rambutmu"(2021). This research is a qualitative research by utilizing the approach of radical feminism, the concept of sexual violence, and victim blaming. The results of this study indicate that women's efforts to be free from victim blaming in sexual violence can be done by presenting a positive combination of femininity and masculinity in women. Instead of maintaining femininity but still subject to patriarchal power, women in short stories ultimately choose to act beyond sex and gender. The release of women from the attachment of femininity, not only allows them to reduce the boundaries as women, but also shows the existence of women's agency to be able to act on an equal footing with men.